Exploration of Reduced Mitochondrial Content–Associated Gene Signature and Immunocyte Infiltration in Colon Adenocarcinoma by an Integrated Bioinformatic Analysis - Kang, Jinlin; li, Na; Wang, Fen; Wei, Yan; Zeng, Yangyang; Luo, Qifan; Sun, Xuehua; Xu, Hui; Peng, Jin; Zhou, Fuxiang (Frontiers in Genetics, 2022)
Purpose: Mitochondria dysfunction refers to cancer immune evasion. A novel 7-gene prognostic signature related to mitochondrial DNA copy number was utilized to evaluate the immunocyte infiltration in colon cancer according to the risk scores and to predict the survival for colon cancer. Experimental design: We performed an integrated bioinformatic analysis to analyzing transcriptome profiling of EB-treated mitochondrial DNA defected NCM460 cell line with differentially expressed genes between tumor and normal tissues of COAD in TCGA. The LASSO analysis was utilized to establish a prognostic signature. ESTIMATE and CIBERSORT validated the differences of immunocyte infiltration between colon cancer patients with high and low risk scores. Results: Our study identified a 7-gene prognostic signature (LRRN2, ANKLE1, GPRASP1, PRAME, TCF7L1, RAB6B and CALB2). Patients with colon cancer was split into high- and low- risk group by the risk scores in TCGA (training cohort: HR=2.50 p < 0.0001) and GSE39582 (validation cohort: HR=1.43 p < 0.05). ESTIMATE and CIBERSORT revealed diverseness of immune infiltration in the two group, especially down-regulated T cell infiltration in the patients with high-risk scores. Finally, we validated the colon patients with low expression of mitochondria number biomarker TFAM had less CD3+ and CD8+ T cell infiltration in clinical specimens. Conclusions: A mtDNA copy number related 7-gene prognostic signature was investigated and evaluated, which may help to predict prognosis of colon cancer patients and to guide clinical immunotherapy via immunocyte infiltration evaluation.